Disease Modeling of Neuropsychiatric Brain Disorders Using Human Stem Cell-Based Neural Models - Kaindl, Johanna; Winner, Beate (Behavioral Neurogenomics, 2019)
Human pluripotent stem (PS) cells are a relevant platform to model human-specific neurological disorders. In this chapter, we focus on human stem cell models for neuropsychiatric disorders including induced pluripotent stem (iPS) cell-derived neural precursor cells (NPCs), neurons and cerebral organoids. We discuss crucial steps for planning human disease modeling experiments. We introduce the different strategies of human disease modeling including transdifferentiation, human embryonic stem (ES) cell-based models, iPS cell-based models and genome editing options. Analysis of disease-relevant phenotypes is discussed. In more detail, we provide exemplary insight into modeling of the neurodevelopmental defects in autism spectrum disorder (ASD) and the process of neurodegeneration in Alzheimer's disease (AD). Besides monogenic diseases, iPS cell-derived models also generated data from idiopathic and sporadic cases.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Disease modeling; hiPSC-derived neurons; hiPSCs; Neuropsychiatric disorders; Organoids